Correction: Hygienic disposal of stools and risk of diarrheal episodes among children aged under two years: Evidence from the Ghana Demographic Health Survey, 2003-2014. - John Tetteh; Isaac Adomako; Emilia Asuquo Udofia; Elom Yarney; Henry Quansah; Anita Ohenewa Yawson; Akye Essuman; Alfred Edwin Yawson (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0266681.].